Experimental study on micro machining of SS304 by using electric discharge machining. (2018) - Ravi Kumar, M.; Krishnaiah, A.; Shankar Kalva, Ravi
Abstract: Electric discharge machining is an electro thermal non traditional machining process where electrical energy is used to generate electrical spark and material removal occurs mainly due to thermal energy of the spark. EDM is used to machine the austenite stainless steel (304, 316, 302), Ferrite S.S. (430, 444, Cr12), Titanium, Copper, Copper alloy, Tool steel, Nickel, Chromium alloy. SS 304 is the basic grade of stainless steel. It is having Good corrosion resistance, electrical conductivity and very good mechanical strength and creep resistance. It is generally used in Pipe and heat exchanger tubes for chemical and petrochemical industries and for boilers. In the present work deals with the central-composition design (CCD)-RSM of three factors with five levels was used to design the experiments. The experiments carried out on die sinker EDM. The experiments were carried out to study the effect of process parameters such as current, pulse on time and pulse off time on responses such as MRR, TWR and Circularity on SS 304. In this paper an attempt has made to develop mathematical model for relating MRR, TWR and circularity to the input process parameters. Experimental results shows Current are the most significant factor for analyzing MRR and TWR. Pulse off time most significant factor for circularity.